Melatonin-Mediated Sugar Accumulation and Growth Inhibition in Apple Plants Involves Down-Regulation of Fructokinase 2 Expression and Activity - Yang, Jingjing; Zhang, Chunxia; Wang, Zhengyang; Sun, Simin; Zhan, Ruiling; Zhao, Yuyue; Ma, Baiquan; Ma, Fengwang; Li, Mingjun (Frontiers in Plant Science, 2019)
Melatonin has been reported to play roles in regulating carbohydrate levels and plant growth. However, little is known about the exact mechanism by which melatonin regulates sugar levels and growth in plants. In this study, it was found that high levels of melatonin inhibited the growth of wild-type apple plants and induced significant accumulations of fructose, glucose and sucrose in apple leaves, while MdFRK2 expression was significantly downregulated. MdFRK2 promoter transiently expressed in tobacco leaves further supported that the expression of MdFRK2 could be inhibited by exogenous melatonin. After applying exogenous melatonin, the suppression of MdFRK2 expression was significantly rescued in transgenic apples overexpressing MdFRK2 via the 35S promoter. Fructose, glucose and sucrose concentrations increased less as compared to wild-type apple plants. Wild-type plants showed a stunted phenotype 21 days after melatonin treatment, while MdFRK2-overexpressing plants exhibited slightly inhibited growth, indicating that the downregulated MdFRK2 expression in response to melatonin was involved in melatonin-mediated growth inhibition. Taken together, these results demonstrate the involvement of MdFRK2 in melatonin-induced sugar accumulation and growth inhibition. Our findings shed light on the roles played by MdFRK2 in connecting melatonin action and plant growth.